POS and Psychological Empowerment as Moderating Variables on the Effect of Job Insecurity on Employee Performance in Islamic Banks - Sania Rahmawati; Muhammad Zakiy (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Abstract. Employee performance in a company is an important component. The occurrence of the COVID-19 pandemic has caused employees to feel job insecurity due to the rise of layoffs in various sectors. This will indirectly affect the performance of employees in a company so that the performance of the company will decrease. For this reason, perceived organizational support and psychological empowerment are needed to reduce the negative effect of job insecurity on employee performance. This study aims to examine the effect of job insecurity on employee performance with perceived organizational support and psychological empowerment as moderating variables. This study uses descriptive quantitative research methods. Data were collected using a questionnaire via google form and distributed to employees who work at Bank Syariah Indonesia, Bank Muamalat, and Bank Madina Syariah. The questionnaire collected was 252 and analyzed using MRA (Moderate Regression Analysis) to test the hypothesis with the SPSS version 24 application. Research shows that there is a negative influence between job insecurity on employee performance, perceived organizational support could moderate the relationship between job insecurity and employee performance, and psychological empowerment is not able to moderate the effect of job insecurity on employee performance. Keywords: Employee performance; job insecurity; moderating role; perceived organizational support, psychological empowerment Abstrak. Kinerja karyawan dalam sebuah perusahaan merupakan komponen penting. Terjadinya pandemic covid-19 menyebabkan karyawan merasakan job insecurity akibat maraknya kasus PHK pada berbagai sektor. Hal tersebut secara tidak langsung akan mempengaruhi kinerja karyawan pada sebuah perusahaan sehingga performa dari perusahaan akan menurun. Untuk itu, diperlukan perceived organizational support dan psychological empowerment untuk menurunkan pengaruh negative job insecurity terhadap kinerja karyawan. Penelitian ini bertujuan untuk menguji pengaruh job insecurity terhadap kinerja karyawan dengan perceived organizational support dan psychological empowerment sebagai variabel moderasi. Penelitian ini menggunakan metode penelitian kuantitatif deskriptif. Data dikumpulkan menggunakan kuesioner melalui googleform dan didistribusikan pada karyawan yang bekerja di Bank Syariah Indonesia, Bank Muamalat, dan Bank Madina syariah Kuesioner yang terkumpul sebanyak 252 responden, dan dianalisis menggunakan MRA (Moderate Regression Analysis) untuk menguji hipotesis dengan aplikasi SPSS versi 24. Hasil penelitian menunjukkan adanya pengaruh negatif antara job insecurity terhadap kinerja karyawan, perceived organizational support mampu memoderasi hubungan job insecurity dengan kinerja karyawan, dan psychological empowerment tidak mampu memoderasi pengaruh job insecurity terhadap kinerja karyawan. Kata kunci: Dukungan organisasi; ketidakamanan kerja; kinerja karyawan; pemberdayaan psikologis; peran moderasi